If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(9 + -3b) = 36 (9 * 4 + -3b * 4) = 36 (36 + -12b) = 36 Add '-36' to each side of the equation. 36 + -36 + -12b = 36 + -36 Combine like terms: 36 + -36 = 0 0 + -12b = 36 + -36 -12b = 36 + -36 Combine like terms: 36 + -36 = 0 -12b = 0 Solving -12b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '-12'. b = 0 Simplifying b = 0
| 150x+72=240x+54 | | c=150-240 | | 4+6u=-2 | | .5y=19.5 | | x=72+45 | | ln(x+4)-ln(10)=ln(12) | | 6+n+14=0 | | -5-4x-7x=1 | | 18p+11+3=12 | | 21=2(x-8)+3x | | -46=3x+8 | | 11+6n= | | 11+5n= | | -120=10+10x | | 21=13w-5 | | 9a-6=5a-14 | | 10p-7=-17 | | 10+5n= | | -7v+4=-17 | | 4(1-3n-14)=4(2n+3)-9 | | 5x-2=3x+18 | | 11=-2-r | | 2y-7=3 | | 65=9m+2 | | 40+5x=340-45x | | 12+5n= | | 7n-2(n+5)=3n-16 | | 8x-3x+4=-36 | | .6n=-15 | | .50r+2(.75r-1)=.25r+6 | | 150+72x=240+54x | | 2(7n-1)=3(5-n) |